Predictive value of physical and blood examination findings for short-term mortality in dogs with respiratory disorders - Muryo Miki; Keiichiro Mie; Hidetaka Nishida; Hideo Akiyoshi; Toshiyuki Tanaka (PLoS ONE, 2025)
Background Similar to human medicine, attempts have been made in veterinary medicine to assess the severity of respiratory disorders using methods other than respiratory function evaluation; however, such approaches remain insufficient. Measurements and main results Medical records at a single small animal private referral center for emergency care were reviewed to identify dogs with respiratory disorders diagnosed by radiography during 2016–2019. The variables of screening test evaluated in this study included patient characteristics, physical examination, and blood test findings. The cases were also divided into Survivors, which were defined as dogs surviving over 7 days from the first consultation day, and Non-survivors, including the dogs euthanized and died naturally within 7 days from the consultation day. In univariate analysis, heart rates, body temperature, white blood count (WBC), glucose, blood urea nitrogen (BUN), phosphate and lactate were significantly different between Survivors and Non-survivors. Multiple logistic regression model with these significant variables revealed that only phosphate was associated with a poor prognosis. Conclusions This study has demonstrated several parameters of physical examination and blood test, especially plasma phosphate concentration, could be related with mortality in canine respiratory disorders. Although further studies are needed, these parameters may enable more accurate assessment of the severity of respiratory disorders in dogs by combining with the conventional assessments of respiratory functions including oxygenation and ventilation.